Transnational Policing after the 1848–1849 Revolutions: The Habsburg Empire in the Mediterranean. (July 2020) - Aliprantis, Christos
Abstract: This article investigates the policing measures of the Habsburg Empire against the exiled defeated revolutionaries in the Mediterranean after the 1848–1849 revolutions. The examination of this counter-revolutionary policy reveals the pioneering role Austria played in international policing. It shows, in particular, that Vienna invested more heavily in policing in the Mediterranean after 1848 than it did in other regions, such as Western Europe, due to the multitude of 'Forty-Eighters' settled there and the alleged inadequacy of the local polities (e.g., the Ottoman Empire, Greece) to satisfactorily deal with the refugee question themselves. The article explains that Austria made use of a wide array of both official and unofficial techniques to contain these allegedly dangerous political dissidents. These methods ranged from official police collaboration with Greece and the Ottoman Empire to more subtle regional information exchanges with Naples and Russia. However, they also included purely unilateral methods exercised by the Austrian consuls, Austrian Lloyd sailors and ship captains, and ad hoc recruited secret agents to monitor the émigrés at large. Overall, the article argues that Austrian policymakers in the aftermath of 1848 invented new policing formulas and reshaped different pre-existing institutions (e.g., consuls, Austrian Lloyd), channelling them against their opponents in exile. Therefore, apart from surveying early modes of international policing, this study also adds to the discussion about Austrian (and European) state-building and, furthermore, to the more specific discussion of how European states dealt with political dissidents abroad in the nineteenth century.